When the drama club is not enough : lessons from the Safe Schools Program for Gay and Lesbian Students - Perrotti, Jeff (Beacon Press, 2002)
Presents stories and strategies learned by the authors while creating a program for Massachusetts's public schools the would promote a safe andwelcoming atmosphere for gay and lesbian students in grades K-12.